Relationship between high trait anxiety in 22q11.2 deletion syndrome and the difficulties in medical, welfare, and educational services. Issue 1 (13th February 2023) - Nakajima, Naomi; Tanaka, Miho; Kanehara, Akiko; Morishima, Ryo; Kumakura, Yousuke; Ohkouchi, Noriko; Hamada, Junko; Ogawa, Tomoko; Tamune, Hidetaka; Nakahara, Mutsumi; Mori, Shunsuke; Ichihashi, Kayo; et al.
Abstract: Aim: The 22q11.2 deletion syndrome (22q11DS) is associated with a high prevalence of mental health comorbidities. However, not enough attention has been paid to the elevated prevalence of high trait anxiety that begins early in life and may be enduring. We sought to identify specific medical, welfare, or educational difficulties associated with high trait anxiety in 22q11DS. Methods: A questionnaire‐based survey was conducted for the parents of 22q11DS individuals ( N  = 125). First, a multiple regression analysis was conducted to confirm the hypothesis that high trait anxiety in individuals with 22q11DS would be associated with parents' psychological distress. This was based on 19 questionnaire options regarding what difficulties the parents currently face about their child's disease, characteristics, and traits. Next, we explored what challenges faced in medical, welfare, and educational services would be associated with the trait anxiety in their child. Results: The multiple regression analysis confirmed that the high trait anxiety was significantly associated with parental psychological distress ( β  = 0.265, p  = 0.018) among the 19 clinical/personal characteristics of 22q11DS. Furthermore, this characteristic was associated with various difficulties faced in the medical care, welfare, and education services, and the parent–child relationship. Conclusion: To our knowledge, this is the first study to clarify quantitatively how the characteristic of high anxiety level in 22q11DS individuals is related to the caregivers' perceived difficulties in medical, welfare, and educational services. These results suggest the necessity of designing service structures informed of the fact that high trait anxiety is an important clinical feature of the syndrome.